A dimensão geográfica de políticas públicas: o Programa de Aquisição de Alimentos (PAA) e a Política Nacional de Economia Solidária (ECOSOL) no Rio Grande do Norte - Leandro de Castro Lima; Lorene K. Barbosa Brasil; Celso Donizete Locatel (Confins)
In general, in the human sciences, and more specifically in the geographical science, the analysis of public policies has been happening in a superficial way, leaving aside normative, economical, political, social, structural, operational and even ideological aspects. All those factors flows throughout the policies, from it conception until the execution, then the importance of considering them. This article has therefore for objective to propose elements for the analysis of public policies as intrinsic instrument to the territory and that it is part of the dynamics of the places, considering for this article the public policies for the countryside, especifically the Program of Food Acquisition (PAA) and the National Politics of Solidary Economy, and the deployment of the same ones in Rio Grande do Norte Stata. In this sense, we believed in the importance of the geography in the context of those analyses, because the public policies, beyond a theoretical-normative approach, has impacts of several orders and it is materialized in different ways on the field.